Discovery of a Manduca sexta Allatotropin Antagonist from a Manduca sexta Allatotropin Receptor Homology Model - Kai, Zhen-Peng (Molecules, 2018)
Insect G protein coupled receptors (GPCRs) have important roles in modulating biology, physiology and behavior. They have been identified as candidate targets for next-generation insecticides, yet these targets have been relatively poorly exploited for insect control. In this study, we present a pipeline of novel Manduca sexta allatotropin (Manse-AT) antagonist discovery with homology modeling, docking, molecular dynamics simulation and structure-activity relationship. A series of truncated and alanine-replacement analogs of Manse-AT were assayed for the stimulation of juvenile hormone biosynthesis. The minimum sequence required to retain potent biological activity is the C-terminal amidated octapeptide Manse-AT (6–13). We identified three residues essential for bioactivity (Thr(4), Arg6 and Phe(8)) by assaying alanine-replacement analogs of Manse-AT (6–13). Alanine replacement of other residues resulted in reduced potency but bioactivity was retained. The 3D structure of the receptor (Manse-ATR) was built and the binding pocket was identified. The binding affinities of all the analogs were estimated by calculating the free energy of binding. The calculated binding affinities corresponded to the biological activities of the analogs, which supporting our localization of the binding pocket. Then, based on the docking and molecular dynamics studies of Manse-AT (10–13), we described it can act as a potent Manse-AT antagonist. The antagonistic effect on JH biosynthesis of Manse-AT (10–13) validated our hypothesis. The IC(50) value of antagonist Manse-AT (10–13) is 0.9 nM. The structure-activity relationship of antagonist Manse-AT (10–13) was also studied for the further purpose of investigating theoretically the structure factors influencing activity. These data will be useful for the design of new Manse-AT agonist and antagonist as potential pest control agents.